1998
DOI: 10.1002/(sici)1099-1581(199803)9:3<169::aid-pat740>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Increased glass transition temperature in motionally constrained semicrystalline polymers

Abstract: semicrystalline polymers poly (-caprolactam) (nylon-6) and poly (ethylene terephthalate) (PET).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 44 publications
2
64
0
Order By: Relevance
“…This rise can be attributed to the increase of the degree of crystallinity due to retrogradation, which correlates with the A : AP ratio. Increase of the degree of crystallinity in semi-crystalline polymer, interacting via hydrogen bonding, is known to increase the glass transition temperature (Jonas and Legras, 1993;Aharoni, 1998;Mano et al, 2005;Yee-Chan et al, 2007).…”
Section: Degree Of Gelatinization (Dg)mentioning
confidence: 99%
“…This rise can be attributed to the increase of the degree of crystallinity due to retrogradation, which correlates with the A : AP ratio. Increase of the degree of crystallinity in semi-crystalline polymer, interacting via hydrogen bonding, is known to increase the glass transition temperature (Jonas and Legras, 1993;Aharoni, 1998;Mano et al, 2005;Yee-Chan et al, 2007).…”
Section: Degree Of Gelatinization (Dg)mentioning
confidence: 99%
“…These are typically low molecular weight compounds able to improve processing conditions by increasing the free volume between polymer chains, thus lowering the melt viscosity or the Tg of the polymer. Consequently, they can soften the polymer and improve the flexibility and properties of the final product [26]. Commonly used plasticizers Q6 include triethyl citrate, tributyl citrate, triacetin, poly(ethylene glycol) (PEG) and poly(propylene glycol) [27].…”
Section: Polymers Used In Hmementioning
confidence: 99%
“…Previous studies demonstrated that a number of factors with synergic effect determine the degradation rate, including hydrophilicity, crystallinity, molecular weight, glass transition temperature and the bulk sample dimensions [35,36]. It should be pointed out that the diffusion of water into polymer matrix is a key step during degradation process.…”
Section: Mechanism Analysis Of Enzymatic Degradationmentioning
confidence: 99%